Effect of epidemiological parameters on severity of early blight of tomato - M.C. KAVYASHREE, R.S. ROOPA, K.B. YADAHALLI* and (Indian Phytopathology, 2016)
Tomato (Lycopersicon esculentum Mill) belongs to the family Solanaceae that originated in the Andian region of South America. Alternaria blight is an important disease. Early blight also known as target spot disease incited by Alternaria solani (Ellis and Martin) Jones and Grout is one of the world’s most catastrophic disease.Aerobiological studies on early blight were carried out to understand the epidemiology of Alternaria blight of tomato during 2011. The studies included trapping of conidia on a vaseline coated glass slide from the tomato field at different intervals, assessing spore load and PDI at different intervals and correlation with meteorological parameters that influence the spore load accumulation and disease development. The weather studies revealed that per cent disease index (PDI) was progressing at linear rate throughout the plant growth and it was negatively correlated with minimum temperature, relative humidity (morning and evening) and rainfall. While, positively correlated with maximum temperature. The aerobiology studies for trapping spore load of Alternaria solani in the open air was found maximum during October and November months. Maximum temperature had positive correlation, while minimum temperature and evening relative humidity had significant negative correlation with spore load.